An innovative procedure to mechanical characterization of repairing materials under vehicle-induced vibrations. (June 2020) - Fossetti, Marinella; Macaluso, Giuseppe; Siciliano, Alfio Francesco; Basone, Francesco; D'Arenzo, Giuseppe
Abstract: If the repairing process of existing bridges takes place without their complete closure, the used materials are subjected vehicle-traffic vibrations during the setting phases. To analyse the influence of vibrations on the mechanical properties of repairing materials, in this study, an experimental investigation on high performance mortars subjected to induced vibrations was carried out. Experimental tests were performed on cubic and prismatic specimens with two kind of fibers. The experimental results showed that vibrations reduce compression strength while the traffic-induced vibrations appear to have not detrimental effects on tensile behavior which is strongly influenced by mechanical characteristics of fibers.